Upgrading of oil palm empty fruit bunch to value-added products - Mohamed, M. (Springer International Publishing, 2014)
As the second largest producer of palm oil in the world, Malaysia generates a substantial amount of oil palm biomass as agricultural wastes in the forms of empty fruit bunches, shell and fiber, fronds, leaves, and trunks. This biomass feedstock has long been identified as a sustainable source of renewable energy which could reduce the dependency on fossil fuels as the main source of the energy supply and thus lead to reduction of greenhouse gases emission. This chapter highlights the application of oil palm biomass as value-added product and specifically demonstrates the capability of empty fruit bunch as renewable source in generating bio-oil which later could be upgraded as biofuel. Green extraction technique known as supercritical fluid extraction using supercritical CO2 (SC-CO2) was implemented in this study. Effects of two extraction conditions were investigated which includes temperature (60-80Â°C) and CO2 flow rate (3-6 mL/min). The extraction was conducted for 2 h using 10 g of OPEFB within particle size 0.15 mm. The crude bio-oil obtained in this study was diluted in 10 mL dichloromethane (DCM) for analysis using gas chromatography-mass spectrometry (GC-MS). Hexadecanoic acid (palmitic acid, C16), dodecanoic acid 1, 2, 3-propanetriyl ester (glycerol trilaurate, C39), and 6 octadecanoic acid (stearic acid, C18:0) were identified as the major compounds. Â© 2014 Springer International Publishing Switzerland. All rights reserved.